SARTRE'S EXISTENTIALISM IN HERMAN MELVILLE'S MOBY DICK - Ambar Andayani (Anaphora : Journal of Language, Literary, and Cultural Studies, 2018)
From the perspective of Sartre’s existentialism, it can be concluded that Ahab is nothing else but what he makes of himself. Through what he does against that white whale, he gets his meaningful existence. Ahab exists only to the extent that he fulfills himself. Ahab gets happiness with his plan and act to kill his mighty woe. Furthermore Ahab’s decision at the same time creates an image of man that in general will do the same thing.